Glacier-level and gridded mass change in river sources in the eastern Tibetan Plateau region (ETPR) from the 1970s to 2000 - Y. Zhu; Y. Zhu; S. Liu; S. Liu; J. Wei; K. Wu; K. Wu; T. Bolch; J. Xu; W. Guo; Z. Jiang; F. Xie; et al. (Earth System Science Data)
The highly glacierized eastern part of the Tibetan Plateau is the key source region for seven major rivers: the Yangtze, Yellow, Lancang–Mekong, Nu–Salween, Irrawaddy, Ganges, and Brahmaputra rivers. These rivers are vital freshwater resources for more than 1 billion people downstream for their daily life, irrigation, industrial use, and hydropower. However, glaciers have been receding during recent decades and are projected to decline further, which will partly and temporarily impact water availability during drought periods, especially in headwater catchments of these larger river systems. Although few studies have investigated glacier mass changes in these river basins since the 1970s, they are site- and period-specific and limited by data availability. Hence, knowledge of glacier mass changes is especially lacking for the years prior to 2000. We therefore used digital elevation models (DEMs) derived from large-scale topographic maps based on aerial photogrammetry from the 1970s and 1980s and compared them to the Shuttle Radar Topography Mission (SRTM) DEM to provide a complete picture of mass change in glaciers in the region. The mass changes are presented on individual glacier bases with a resolution of 30 m and are also aggregated into gridded format at a resolution of 0.5°. Our database consists of 13 117 glaciers with a total area of ∼ 21 695 km2. The annual mean mass loss of glaciers is −0.30 ± 0.13 m<mspace width="0.125em" linebreak="nobreak"/>w.e.<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="32pt" height="8pt" class="svg-formula" dspmath="mathimg" md5hash="037cb71ee4aad448addf7fb9b3a7456d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-17-1851-2025-ie00001.svg" width="32pt" height="8pt" src="essd-17-1851-2025-ie00001.png"/></svg:svg> in the whole region. This is larger than the previous site-specific findings: the surface thinning increases on average from west to east along the Himalayas–Hengduan mountains, with the largest thinning in the Irrawaddy basin. Comparisons between the topographic map-based DEMs and DEMs generated based on Hexagon KH-9 metric camera data for parts in the Himalayas demonstrate that our dataset provides a robust estimation of glacier mass changes. However, the uncertainty is high at high altitudes due to the saturation of aerial photos over low-contrast areas like a snow surface on a steep terrain. The dataset is well-suited to supporting more detailed climatical and hydrological analyses and is available at https://doi.org/10.11888/Cryos.tpdc.301236 (Liu et al., 2024).